2007
DOI: 10.1111/j.1750-3841.2007.00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Microbial Population within a Hot‐Drinks Vending Machine and the Microbial Load of Vended Hot Chocolate Drink

Abstract: In order to understand the development of the microbial population within a hot-drinks vending machine a new machine was placed in a staff area of a university campus vending only hot chocolate. The machine was cleaned weekly using a detergent based protocol. Samples from the mixing bowl, dispense area, and drink were taken over a 19-wk period and enumerated using plate count agar. Bacillus cereus was identified using biochemical methods. Vended drinks were sampled at 0, 3, 6, and 9 min after vending; the hot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 4 publications
1
15
0
Order By: Relevance
“…There has been one published case of bacterial food poisoning from a hot-drinks vending machine. Nelms (Nelms et al, 1997) reported on a case of food poisoning (Bacillus Cereus) in a Minneapolis manufacturing plant, where employees reported vomiting and nausea after drinking hot chocolate from a vending machine based in the plant cafeteria (Hall et al, 2007). In Italy the provision of food and beverages through This system identifies the risks for human health and the safety and preventive measures for their elimination and/or their control (Dragoni & Bonomi, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There has been one published case of bacterial food poisoning from a hot-drinks vending machine. Nelms (Nelms et al, 1997) reported on a case of food poisoning (Bacillus Cereus) in a Minneapolis manufacturing plant, where employees reported vomiting and nausea after drinking hot chocolate from a vending machine based in the plant cafeteria (Hall et al, 2007). In Italy the provision of food and beverages through This system identifies the risks for human health and the safety and preventive measures for their elimination and/or their control (Dragoni & Bonomi, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In Italy the provision of food and beverages through This system identifies the risks for human health and the safety and preventive measures for their elimination and/or their control (Dragoni & Bonomi, 2008). Kassa et al (2001) also stated the importance of direct visual inspection, as another measure for preventing potential risk of food-borne illnesses (Hall et al, 2007;Kassa, Harrington, Bisesi, & Khuder, 2001). As mentioned above, previous studies focused on hygiene and contamination of the internal mechanical parts of the vending machines, on the microbiological quality of the powders used to prepare the beverages, and/or on the beverages direct contamination (Hall et al, 2007;Nelms et al, 1997;Vallone & Bonomi, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacillus cereus has been isolated from cocoa, hot chocolate powder and vended hot chocolate drinks (Chung-Wang, Kuo, Lin, Hong, & Tsai, 1993;Gabis, Langlois, & Rudnick, 1970;Hall, Short, Saltmarsh, Fielding, & Peters, 2007;Nelms, Larson, & Barnes-Josiah, 1997). Cocoa and hot chocolate powders have also been found to contain other Bacillus sp., Staphylococcus aureus, yeasts and moulds (ChungWang et al, 1993;Gabis et al, 1970;Payne et al, 1983).…”
Section: Introductionmentioning
confidence: 98%